The Learning Outcomes of Playing Football Through the Small-side Game Learning Model - Suyudi, Imam (Journal of Sport Education, Coaching, and Health (JOCCA), 2023)
The purpose of this study was to determine the results of learning to play football through a small-sided games learning model. This research is a type of classroom action research. The population of this study was students of SMP Negeri 4 Anggeraja Enrekang. The number of students of SMP Negeri 4 Anggeraja Enrekang. The sample selected in this study is representative to represent the students of SMP Negeri 4 Anggeraja Enrekang as a whole. Sampling is done using random sampling techniques. The number of samples used was as many as 40 students. The type of data collected is quantitative data. Following the type of data collected, the analysis of research data is carried out through quantitative analysis using percentages. Quantitative analysis is applied to data on initial test results of football playing skills, evaluation results in the first cycle, and evaluation results in the second cycle. The results of the study concluded that: the application of the small-side game learning model improves the quality of learning as evidenced by the increase in the average ability of basic skills to play football for each student, and learning that was previously centered by the teacher is now reversed to student-centered learning through tournaments or matches between them, the teacher is more of a mediator/facilitator in student teaching and learning activities. The results of student responses to the implementation of the small-side game learning model show that students are happy, motivated to learn, can find new things, and more easily and dare to follow physical education subjects